Penggunaan Metode Demonstrasi Untuk Meningkatkan Motorik Halus Anak Melalui Kegiatan Menjahit Pada Karton di TK Gmim Nazaret Matani Tomohon - Meiske Ester Tumbel (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was carried out at the GMIM Nazaret Matani Tomohon Kindergarten with a background of problems such as children's fine motor skills which are still low which is indicated by the lack of children's skills in sewing activities on cardboard, namely the speed of eye and hand coordination is not yet balanced, children are not yet able to hold and insert threads into the stitching holes. appropriate and the child has not been able to complete the sewing task to completion. To overcome this problem, researchers used the demonstration method in the classroom learning process. This research aims to improve children's fine motor skills through sewing activities on cardboard at the GMIM Nazaret Matani Tomohon Kindergarten. The research method used is classroom action research (PTK) with 4 stages, namely: 1. Planning, 2. Class Action, 3. Observation, 4. Reflection using two cycles. The subjects of this research were 13 group B children. The research results obtained in cycle I were with a percentage of 30.77% and in cycle II there was an increase with a percentage of 84.61%. The conclusion of this research is that the use of the demonstration method in learning activities to sew on cardboard at the GMIM Nazaret Matani Tomohon Kindergarten can improve children's fine motor skills. And it is recommended for kindergarten teachers to improve the quality of learning by using demonstration methods in implementing learning in kindergarten to support the student learning process.